Aplikasi Sistem Informasi Geografis (SIG) untuk Pengelolaan Sumberdaya Mineral di Kabupaten Bombana, Provinsi Sulawesi Tenggara - , BOMA BAGUS PANUNTUN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mineral resources are natural resources that must be managed optimally, efficient, transparent, sustainable and environmentally friendly also equitable in order to obtain the maximum benefit for the prosperity and welfare of the people. One of the areas in Indonesia, which has a large enough potential of mineral resource is Bombana District. Bombana District is one of the districts in the province of Southeast Sulawesi that has the potential of mineral sizable and spread in several subdistrict with the main exploration targets such as gold, nickel, chromite and quartz sand. But during this has not provided an information management system of data management for effective and efficient management of mineral resources on Bombana District. The purpose of this research is to build a database of mining business license (IUP) for mineral resources with applications of geographic information systems (GIS) in Bombana District and to inventory the potential and the type of mineral resources using GIS applications with existing tabular data. The method used as an approach in this research is GIS methods which equipped with a field survey. from this study it can be concluded that the IUP of mineral resource spatial database Bombana District can be built with GIS which includes IUP for gold, galena, copper, chromite, nickel, iron sand and quartz sand resources. This database can be easily updated and fixed if there are developments or changes annually or in specific time. GIS technology can be used as an attempt to inventory the potential, type and distribution of mineral resources in Bombana District. Non spatial data (tabular data and report) of the potensial, type and distribution of mineral resources can be changed become data that are spatially (map) so as to facilitate the reading of the data visually. In general, the type of gold deposits in Rarowatu, Rarowatu North, North Poleang, Mataosu, Lentari Jaya, Eastern part of Tontonunu area is placer gold with varying content. In some places also showed indications of primary gold deposits with unknown contents. Although not as a whole, but the deposition of nickel laterite indications show that in some locations found Ni (nickel) content more than 1% with thickness of the laterite is generally more than two meters. The locations that indicates the existence of nickel laterite which has good potential exist on the Kabaena Island. Galena are found in the northwestern part of Rarowatu area directly adjacent to the North Poleang. Copper are found in Central Part of Kabaena area. Iron sand are found in the Northern part of North Poleang area bordered by Mataosu and Northern part of Central Kabaena. Chromite are found in Batuawu-Pangkalaero-Purano areas. Quarzt sand are found in Waemputtang-Padang Paâjongangâe areas of East Poleang Subdistrict and Rakadua area of West Poleang Subdistrict with spread of up to tens thousands of hectare and a thickness up to tens of meters.